Audit Forensik dan Bukti Digital dalam Mengungkap Kasus Korupsi BTS Kominfo 2023 - Syabilal Ali; Handar Subhandi Bakhtiar (STIKes Ibnu Sina Ajibarang, 2025)
The corruption case in Indonesia, specifically the BTS project scandal by the Ministry of Communication and Informatics, reflects serious challenges in public financial management. According to information from Transparency International, Indonesia still ranks as a country with a high level of corruption. The BTS project, aimed at improving internet access in remote areas, has been revealed to suffer from budget misuse and corrupt practices by high ranking officials. To address this issue, forensic audits and digital evidence have become crucial tools in uncovering crimes. However, challenges such as a lack of trained human resources, limited technological infrastructure, and inter-agency coordination hinder the effectiveness of law enforcement. Integrated efforts to enhance the capacity of law enforcement and technological infrastructure are needed to effectively combat corruption and create a clean and transparent government.